2021
DOI: 10.1097/mnm.0000000000001508
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT for the evaluation of male breast cancer: a systematic review

Abstract: BackgroundIn the last years, some studies on the usefulness of 18 F-fluorodeoxyglucose PET/computed tomography ( 18 F-FDG PET/CT) for the evaluation of male breast cancer (MBC) have been produced. The aim of this review is to analyze the usefulness of 18 F-FDG PET/CT and its diagnostic performances for the assessment of MBC.Methods A wide literature search of the PubMed/ MEDLINE, Scopus, Embase and Cochrane library databases was made to find relevant published articles on the role of 18 F-FDG PET/CT for the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In a systematic review by Dondi [ 41 ], which aimed to analyze the diagnostic performance and utility of 18F-FDG PET/CT in the evaluation of MBC, it was found that, despite the limitations of the review, 18F-FDG PET/CT appears to be an effective method for assessing MBC. The conclusion continued with the idea that further research is required to clarify the role of hybrid imaging with 18F-FDG in the evaluation of MBC, particularly in comparison to breast cancer in females.…”
Section: Resultsmentioning
confidence: 99%
“…In a systematic review by Dondi [ 41 ], which aimed to analyze the diagnostic performance and utility of 18F-FDG PET/CT in the evaluation of MBC, it was found that, despite the limitations of the review, 18F-FDG PET/CT appears to be an effective method for assessing MBC. The conclusion continued with the idea that further research is required to clarify the role of hybrid imaging with 18F-FDG in the evaluation of MBC, particularly in comparison to breast cancer in females.…”
Section: Resultsmentioning
confidence: 99%
“…18 F-fluorodeoxyglucose ([ 18 F]FDG) is the most common radiotracer used to perform positron emission tomography/CT (PET/CT) and PET/MRI. At first, this tracer was used mainly for the assessment of neoplastic diseases, given its ability to detect hypermetabolic lesions on the basis of their glycolytic metabolism [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. However, high glucose metabolism characterizes also activated inflammatory cells, and the use of [ 18 F]FDG PET has emerged for the evaluation of infectious and inflammatory diseases [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
mentioning
confidence: 99%